2023
DOI: 10.1186/s12913-023-09277-y
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the struggle of living with type 2 diabetes – diabetes specialist nurses’ and patients’ perspectives on digital interventions

Abstract: Background Diabetes self-management education and support (DSMES) is a cornerstone in the treatment of type 2 diabetes mellitus (T2DM). It is unclear whether delivering DSMES as a digital health intervention (DHI) might meet the needs experienced by patients with T2DM and diabetes specialist nurses (DSN) of the primary health care system in Sweden. Methods Fourteen patients with T2DM and four DSN participated in three separate focus groups: two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…A recent survey showed that the standard of care in T2DM, although generally acceptable, cannot meet the variety of patients' needs in terms of accessibility and timeliness of psychological, emotional, and behavioral support [4]. This unmet need can be alleviated by a wider use of digital technologies designed to help patients with their lifestyle and health-related decisions through making accessible critical data and on-demand consultations [5]. The technologies for managing T2DM include medical devices such as glucose meters, insulin pumps, continuous glucose monitors, and connected insulin pens; digital interventions including mobile smartphone applications (apps), text messaging, electronic communications, and video conference platforms; and wearable technologies for monitoring health, such as activity trackers, sleep trackers, and smartwatches [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey showed that the standard of care in T2DM, although generally acceptable, cannot meet the variety of patients' needs in terms of accessibility and timeliness of psychological, emotional, and behavioral support [4]. This unmet need can be alleviated by a wider use of digital technologies designed to help patients with their lifestyle and health-related decisions through making accessible critical data and on-demand consultations [5]. The technologies for managing T2DM include medical devices such as glucose meters, insulin pumps, continuous glucose monitors, and connected insulin pens; digital interventions including mobile smartphone applications (apps), text messaging, electronic communications, and video conference platforms; and wearable technologies for monitoring health, such as activity trackers, sleep trackers, and smartwatches [6,7].…”
Section: Introductionmentioning
confidence: 99%